Less than full-time training (LTFT), is this the new norm? A cross-sectional study using a UK-wide online survey to evaluate trainees' views and intentions for LTFT. Issue 11 (7th November 2022) - Cathcart, Jennifer; Mayne, Kaitlin J; Hull, Richard; Jones, Michael; Miller, Alastair
Abstract : Objectives: Interest in less than full-time training (LTFT) is growing among doctors in training. LTFT applications have previously been limited to fulfilment of specific criteria such as childcare or health reasons, but Health Education for England (HEE) has recently completed a pilot into LTFT for a third category: lifestyle choice. This was recognised as an opportunity to canvas trainee perspectives and intentions on LTFT and implications for workforce planning. Design: A cross-sectional study of UK trainees via an online questionnaire. Setting/participants: The survey was distributed via email to trainees in all specialities and stages of training across the UK. The survey focused on three key themes: experiences of current LTFT trainees, perspectives of trainees considering LTFT in the future and experience of working with LTFT colleagues. Results: Responses were received from 783 trainees across the UK, with most responses received from physician trainees (76%). Current LTFT trainees represented one-third of respondents. Of those not currently working LTFT, 75% expressed an intention to do so in future with lifestyle being the most common reason. Almost half of this group were concerned about the impact on their training. Stigma, reduced training opportunities, prolonged training and the application process were commonly cited barriers. These difficulties were experienced by several current LTFT trainees, 32% of whom described a negative impact on their training. Almost two-thirds (62%) of respondents stated they wish to work LTFT as a consultant. Conclusion: Systems must adapt to increase access to LTFT training to promote trainee well-being and retention. Progress is being made and we suggest HEE's category three pilot be rolled out across the UK as a priority. Workforce planning needs to consider the substantial rise in popularity of LTFT among trainees to offset any shortfalls in the present and future workforce.